Principles of constraint programming - Apt, Krzysztof R., 1949- (Cambridge University Press, 2003)
Methods to solve constraint problems (e.g. scheduling) rely on the idea of constraint propagation and search. Using constraint techniques in programming environments has accelerated the solution process, combining ideas from artificial intelligence, programming languages, databases, and operational research. This text is a modern, multidisciplinary introduction covering both foundations and applications.